Conhecimento tradicional de pescadores : migração reprodutiva e percepções sobre abundância dos peixes comerciais do Rio Cuiabá – MT - Almeida, Suzanne Estéfanie (2016)
This study aims: i- to describe the dynamics of reproductive migration of commercial fish of the Characiform orders and Siluriforme orders; ii- to verify the perception of fishermen about the current situation and variations of the fish stocks of the main commercial species of the Cuiabá river; and, iii- to determine which factors could be related to these variations from the perspective of the respondents. A total of 179 fishermen were interviewed. These were located in three sections of the Cuiabá River: upriver (between the municipality of Nobres will Acorizal); medium course (between the city of Cuiaba and Barranco Alto community in Santo Antônio do Leverger); downriver (Between Barra do Aricá community in Santo Antonio Leverger and Barão de Melgaço). Semi-structured questionnaires with standardized questions about the 12 main commercial species migrating pto reproduce in the basin of the Cuiabá River were applied. As for reproductive dynamics, fishermen failed to precisely define the reproductive migration period, inferred from fish schools formation, since this is a process that takes place simultaneously with the trophic migration. However, respondents indicated unanimously that Characiforms begin their migration before Siluriforms. The perception of the fishermen is that migratory fishes spawn p in the main channel of the rCuiabá River and in the Pantanal shallow lakes when, in the literature. these are identified as initial development areas,. As for fish stocks, it was possible to rapidly obtain information that is the most recent about these species’ stocks. The fishermen perceptions that Pacu, Cachara and Barbado might be overexploited corroborate the literature. Furthermore, the traditional knowledge of the fishermen shed light, for the first time, on the stocks status of two other commercial species, namely, Pacupeva and Piava. For the respondents f the stocks of commercial fishes varied greatly over the years, and these fluctuations were linked to the construction of – a dam on the Manso River, the principal affluent of the Cuiabá. For them, the impacts were larger in the early years after the dam’s contruction, but still affect the stock due to changes in the river maximum peak stages .. Gaining access to the traditional knowledge of the fishermen allowed to obtain reliable information, the most recent available, on the status of commercial species in the Cuiabá River Basin. This knowledge can be useful to the development of management programs, or of use to government agencies, and can be the starting point for further more in depth studies.